Institutionalizing youth aspirations in the public policy process in Egypt - Ibrahim, Mohamed Kadry (AUC Knowledge Fountain, 2015)
After leading change in the 2011 revolution, and being the majority of the Egyptian population, young Egyptians became the focus of much attention. Youth empowerment and participation in shaping the future of their country became one of the primary concerns after the revolution. The research purpose is to identify the extent to which youth aspirations and dreams are incorporated in the process of public policy making. The research takes the Ministry of Youth and Sports and Ministry of Manpower and Migration as a case study to see their role and experience in institutionalizing youth aspirations in the national public policy and the challenges involved in this process. The study particularly addresses the activities that took place towards this objective with particular focus on the Egyptian Youth Parliament at Ministry of Youth and Sports and the Development of the National Action Plan for youth Employment at Ministry of Manpower and Migration. In addition, the study dwells into how civil society organizations, both local and international, perceive the efforts done towards this objective and their contribution in the process. The study builds on qualitative research methods in the form of in-depth interviews, and desk review of reviews related to national youth policies. The interviews were conducted with different stakeholders that were both influenced by and influencing the issue of focus in the current situation. These include: Representatives from the Ministry of Youth, Ministry of Manpower and Migration, civil society organizations, and from International Organizations. The analysis shows that we lack in Egypt any institutional framework to include youth aspirations in the public policy process, yet there are some successful experience that can be replicated with the support of the international organizations and civil society. The thesis proposed a set of recommendations that could provide an institutional mechanism and framework to make sure youth aspirations are always included in the policy process.